2023
DOI: 10.3390/molecules28073008
|View full text |Cite
|
Sign up to set email alerts
|

Naphth[1,2-d]imidazoles Bioactive from β-Lapachone: Fluorescent Probes and Cytotoxic Agents to Cancer Cells

Abstract: Theranostics combines therapeutic and imaging diagnostic techniques that are extremely dependent on the action of imaging agent, transporter of therapeutic molecules, and specific target ligand, in which fluorescent probes can act as diagnostic agents. In particular, naphthoimidazoles are potential bioactive heterocycle compounds to be used in several biomedical applications. With this aim, a group of seven naphth[1,2-d]imidazole compounds were synthesized from β-lapachone. Their optical properties and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…13 The selective cytotoxicity toward cancer cells and the fluorescence of naphtho [1,2-d]imidazoles make possible the application of these compounds in antitumor theranostic systems. 14 It was also found that naphtho [1,2d]imidazole derivatives are promising light-emitting materials for OLEDs. 15−17 Naphtho [1,2-d]imidazoles are usually synthesized by condensation of carbonyl compounds with 1,2-diaminonaphthalene derivatives, 8,11,17−19 often formed in situ.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The selective cytotoxicity toward cancer cells and the fluorescence of naphtho [1,2-d]imidazoles make possible the application of these compounds in antitumor theranostic systems. 14 It was also found that naphtho [1,2d]imidazole derivatives are promising light-emitting materials for OLEDs. 15−17 Naphtho [1,2-d]imidazoles are usually synthesized by condensation of carbonyl compounds with 1,2-diaminonaphthalene derivatives, 8,11,17−19 often formed in situ.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, they are nonacidic antiinflammatory agents, antihypertensive agents, , thrombopoietin mimics, potent human histamine H 4 receptor ligands, and HCV NS5A inhibitors . The selective cytotoxicity toward cancer cells and the fluorescence of naphtho­[1,2- d ]­imidazoles make possible the application of these compounds in antitumor theranostic systems . It was also found that naphtho­[1,2- d ]­imidazole derivatives are promising light-emitting materials for OLEDs. Naphtho­[1,2- d ]­imidazoles are usually synthesized by condensation of carbonyl compounds with 1,2-diaminonaphthalene derivatives, ,, often formed in situ. , Intramolecular condensation of 1-amido-2-amino/1-amino-2-amido-naphthalenes is also frequently used. ,,,, Another approach involves the cyclization of 1-aminonaphthalene derivatives containing an N-CRN moiety. In all of the mentioned methods, the assembly of the tricyclic naphtho­[1,2- d ]­imidazole skeleton is completed by the formation of the imidazole ring (imidazole ring-forming strategy) (Scheme , (1a)).…”
Section: Introductionmentioning
confidence: 99%